2011
DOI: 10.1139/x11-133
|View full text |Cite
|
Sign up to set email alerts
|

Movements of wintering American marten (Martes americana): relative influences of prey activity and forest stand age

Abstract: American marten (Martes americana (Turton, 1806)) was traditionally associated with old-growth forests, but recent evidence suggests that they are frequently found in younger forests as well. To better understand habitat requirements by this economically important furbearer, we investigated its fine-scale movement behavior in relation to local prey activity (tracks) and stand age. We georeferenced 34 marten tracks (57 km), associated prey tracks, and subnivean forays in a balsam fir forest of southern Québec, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…CWD provides subnival spaces that can be used by marten [ 69 ]. Subnival spaces are particularly important for prey accessibility and provide protection against predation, together with resting sites for thermoregulation [ 70 – 73 ]. Consequently, habitat use by marten is mainly dependent upon the internal structure of the forest [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CWD provides subnival spaces that can be used by marten [ 69 ]. Subnival spaces are particularly important for prey accessibility and provide protection against predation, together with resting sites for thermoregulation [ 70 – 73 ]. Consequently, habitat use by marten is mainly dependent upon the internal structure of the forest [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study that was conducted in 2016 in New York State [ 77 ], however, showed that occupation of the territory by the fisher was positively influenced by proportions of coniferous and mixedwood forests, but negatively affected by the density and proportion of agricultural environments. Like marten, the fisher likely would be more dependent upon the structure of the forest than on the age or type of settlement [ 22 , 73 75 ]. Participants also pointed out that mustelid habitats were especially consistent with those of their main prey: snowshoe hares, squirrels and other small mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Functional habitat loss relative to seismic lines has also been shown in woodland caribou [ 11 ], and relative to well pads in mule deer [ 30 , 95 ]. However, marten use cut block edges for travel and hunting at least proportionally to availability [ 53 , 96 ] elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…In winter, martens hunt mostly large prey such as Northern flying squirrels (Glaucomys sabrinus), American red squirrels (Tamiasciurus hudsonicus), and snowshoe hares (Lepus americanus) [38] and feed on microtine rodents only incidentally [39]. In our study area, squirrels and hares occurred in similar densities in young, regenerating, and old forest stands [40] and thus prey density in forest is unlikely to have affected our results. However, the lack of foraging opportunities in open areas may have increased movement cost in these habitats.…”
Section: Discussionmentioning
confidence: 97%